Provision of Fitoimun® in Feed for the Growth and Survival of White Snapper (Lates calcarifer) Raised in Silvofishery Ponds in Muara Badak Ulu Village, Muara Badak District, Kutai Kartanegara Regency - Amalia, Rizqi; Hardi, Esti Handayani; Pagoray, Henny (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2024)
This study aims to analyze the effect of adding Fitoimun® as a natural medicine on barramundi/white snapper (Lates calcarifer). Maintenance is carried out for 30 days, white snapper fry measuring 72-103 g with floating net cage containers measuring 4x4 m2 with a stocking density of 14 heads / repeats. The method used in this study was using Complete Randomized Design (RAL) with 3 treatments 3 replications with doses P0: 0 mL/kg feed, P1: 20 mL/kg feed, P2: 24 mL/kg feed. Parameters observed include survival, absolute weight growth, specific growth rate, and feed conversion ratio. The results obtained from the study showed that the administration of Fitoimun® had no real effect, although the application of Fitoimun® dose of 20 mL/kg feed had a survival rate of 100%, absolute weight growth of 78.7g, a specific growth rate of 2.1%, and the best feed conversion ratio of 1.63 than other doses.